ICT Systems Security and Privacy Protection 29th IFIP TC 11 International Conference, SEC 2014, Marrakech, Morocco, June 2-4, 2014, Proceedings - Cuppens-Boulahia, Nora.; Cuppens-Boulahia, Nora.; Cuppens, Frederic.; Cuppens, Frederic.; Jajodia, Sushil.; Jajodia, Sushil.; Abou El Kalam, Anas.; Abou El Kalam, Anas.; Sans, Thierry.; Sans, Thierry. (IFIP Advances in Information and Communication Technology, 2014)
This book constitutes the refereed proceedings of the 29th IFIP TC 11 International Information Security and Privacy Conference, SEC 2014, held in Marrakech, Morocco, in June 2014. The 27 revised full papers and 14 short papers presented were carefully reviewed and selected from 151 submissions. The papers are organized in topical sections on intrusion detection, data security, mobile security, privacy, metrics and risk assessment, information flow control, identity management, identifiability and decision making, malicious behavior and fraud and organizational security.